PENGARUH TINGKAT KESEHATAN BANK SYARIAH TERHADAP RETURN SAHAM BANK - Usamah, Usamah; Fahrunisa, Aliffiana; Edi Purnomo, Djauhar (Neraca, 2023)
This study aims to obtain empirical evidence of the effect of the ratio of NPF, FDR, GCG, ROA, NIM, and CAR on stock returns. The population in this study is Islamic Commercial Banks and Sharia Business Units registered with Bank Indonesia in 2018-2020. The sample for this study was determined by purposive sampling method in order to obtain a sample of 10 BUS and UUS that met the criteria. The data used is secondary data downloaded from the Indonesia Stock Exchange website (www.idx.co.id) and the websites of each company. Analysis of the data used is the multiple linier regression method. The results of this study indicate that partially the NPF, FDR, GCG, NIM, and CAR variabels have no significant effect on stock returns. While the ROA variable has a significant effect on stock returns. Simultancously the variables NPF, FDR, GCG, ROA, NIM, and CAR have a significant effect on stock returns.